2021
DOI: 10.1016/j.jaad.2020.12.089
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and tolerability of tetracyclines and clindamycin plus rifampicin for the treatment of hidradenitis suppurativa: Results of a prospective European cohort study

Abstract: The efficacy and tolerability of tetracyclines and clindamycin plus rifampicin for the treatment of hidradenitis suppurativa; results of a prospective European cohort study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 34 publications
(86 reference statements)
1
60
1
7
Order By: Relevance
“…Commonly used systemic therapies include tetracyclines, dapsone, IV ertapenem and combination therapies of 1) clindamycin and rifampicin or 2) moxifloxacin, metronidazole and rifampicin. 211,212 In addition to the bacteriostatic or bactericidal properties, many antibiotics also have anti-inflammatory properties. Tetracycline antibiotics suppress immune cell chemotaxis and also inhibit matrix metalloproteinase (MMP) activity, 213 which likely contributes to their effectiveness as an HS therapy.…”
Section: The Impac T Of Antib I Oti C S On the S K In Microb I Omementioning
confidence: 99%
“…Commonly used systemic therapies include tetracyclines, dapsone, IV ertapenem and combination therapies of 1) clindamycin and rifampicin or 2) moxifloxacin, metronidazole and rifampicin. 211,212 In addition to the bacteriostatic or bactericidal properties, many antibiotics also have anti-inflammatory properties. Tetracycline antibiotics suppress immune cell chemotaxis and also inhibit matrix metalloproteinase (MMP) activity, 213 which likely contributes to their effectiveness as an HS therapy.…”
Section: The Impac T Of Antib I Oti C S On the S K In Microb I Omementioning
confidence: 99%
“…The results showed no significant differences in efficacy between the two treatments, regardless of the disease severity. 65…”
Section: Treatmentmentioning
confidence: 99%
“…10 A recent multicenter prospective cohort study showed significant decrease in IHS4 from baseline and a 40% of HiSCR achievement after 12-week treatment with tetracycline. 65 Likewise, a retrospective study comparing the efficacy of lymecycline (300 mg daily) versus the combination therapy clindamycin and rifampicin (600 mg plus 600 mg daily) during 10 weeks in 52 patients (26 per group) observed a 57.7% and 53.8% HiSCR achievement, respectively. 66 Clindamycin and rifampicin used at a dose of 300 mg twice daily have been proven effective in HS in several observational studies 65,[67][68][69] and are considered a first-line and second-line treatment for HS.…”
Section: Topical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations